SWOC Analysis of Korangadu pasture land for sheep - Akila, N; Bharathy, N (Indian Farming, 2017)
In India, grazing-based livestock husbandry plays an important role in the rural economy as around 50% of animals depend on grazing. Pasturelands over an area of 12 Mha constitute the main grazing resources that are available. Hence restoration and improvement of the deteriorated korangadu pasture land and their proper management is a must to provide adequate forage and grazing to livestock. Establishing Korangadu pasture land can be tried either if monsoon is abundant or adequate or with irrigation for growth and sustenance. Involving a range of technologies to improve the productivity of grazing lands like reseeding with grasses, introduction of leguminous species, rotational grazing should be tried with proper treatment and follow up. Once established pasture land with tree fodder will serve for 3-5 years with less labour and investment.